Hybrid Nanotube Assembly and Hierarchical ZSM‐23 Zeolite Synthesized with Cationic Polymer and Enhanced Performance in n‐Heptane Hydroisomerization. Issue 9 (5th August 2020) - Tontisirin, Supak; Ernst, Stefan; Wilhelm, Christian
Abstract: Novel nanotube assembly and hierarchical ZSM‐23 zeolite can be fabricated by using the low‐cost and commercial cationic polymer of polydiallyldimethylammonium chloride (polyDDA) in the synthesis gel. In this facile synthesis, the polyDDA plays roles as the growth inhibitor for nanosized crystals and the secondary porogen. This unique crystal structure shows tubular nanocrystals assembling to form agglomerates. This hierarchical structure combines intercrystalline mesopore and narrow macropore to the micropore of ZSM‐23. Double advantages of nanocrystal and hierarchical structure contribute to higher pore mouths and enhanced diffusion of the reaction molecules. The hierarchical form also benefits for simple crystal recovery of nanozeolite by filtration. The n‐heptane hydroisomerization shows the derived Pt/H‐ZSM‐23 outperforms the conventional Pt/H‐ZSM‐23 with higher isomer yield at higher conversion and less cracked product yield. This could be attributed to higher pore mouths and efficient mass transport because of the shorter diffusion path length by the smaller crystal and hierarchical structure supplementing pore‐to‐pore connection of the molecular transport. Abstract : Hybrid nanotubes and a hierarchical ZSM‐23 zeolite was synthesized by using a low‐cost and commercial cationic polymer of polydiallyldimethylammonium chloride in the synthesis gel. The polyDDA acts as growth inhibitor for nanosized crystals and secondary porogen. The double advantages of nanoscale crystal and hierarchical structure can contribute to enhanced performance in n‐heptane hydroisomerization.